Estimation of biochemical and technological indicators of grain of hulled and hulles barley varieties in the conditions of the Middle Volga region - E. N. Shabolkina; S. N. Shevchenko; N. V. Anisimkina (Зерновое хозяйство России, 2023)
In order to use efficiently barley varieties for such purposes as food, fodder and brewing, an objective and thorough study of grain quality is of great necessity, with adjustment for the features of hulles varieties. The purpose of the current study was to estimate the biochemical and technological indicators of grain varieties of hulled and hulles barley, to determine the correlation between quality indicators. On the experimental basis of the Samara Research Institute of Agriculture, there were studied grain quality indicators of hulled and hulles barley varieties of the Competitive Variety Testing in 2019–2021. There has been established a high-protein group of varieties, such as ‘Orlan’, ‘Bezenchuksky 2’, ‘Lun’, ‘Streletsky golozerny’ and ‘Omsky golozerny 1’ with 14.9–16.8 % of protein. The largest ‘1000-grain weight’ (43.7–44.1 g) and low activity of α-amylase in grain (352–421 c of ‘falling number’) over the years of study was established among the hulled barley varieties of this group. Barley varieties with such qualitative traits could be widely used in the food industry and feed production. There has been noted that hulles barley varieties with a high protein percentage (16.8 %), the absence of hulls and low amylolytic activity (471 c), when adapting to growing conditions, will improve not only the quality of cereals, grain fodder, but can also be used for baking purposes. When summarizing the correlation analysis results, there was established that the correlation between a grain protein index and other qualitative traits was identified only under the extremely dry conditions of 2021. Grain husk content closely correlated inversely with grain unit (–0.94**; –0.64*; –0.84**) through all years of study. The ‘falling number’ in 2019 was somewhat less correlated with 1000-grain weight (0.60*) and grain unit (0.61*); negatively correlated with grain husk content both in 2019 and 2020 (–0.65*; –0.82**).